Familial antithrombin III deficiency and Mycoplasma pneumoniae pneumonia. Issue 10 (October 1991) - Creagh, M D; Roberts, I F; Clark, D J; Preston, F E
Abstract : A 10 year old girl presented with a massive femoral vein thrombosis associated with Mycoplasma pneumoniae pneumonia. Subsequently type I familial antithrombin III deficiency was diagnosed. It is suggested that prophylactic measures aimed at preventing thrombosis should be considered in acutely ill subjects with infection and familial thrombophilia.